Use Mobile Apps to Link to Google Forms to Conduct Online Surveys...16th International Congress on Nursing Informatics (NI2024), July 28-31, 2024, Manchester, UK. - Shih-Yuan Chen; Ming-Hsiang Tu (Studies in Health Technology & Informatics, 2024)
The study aimed to evaluate changes in anxiety levels in patients with coronary artery disease before and after cardiac catheterization. The mobile applications LINE and GOOGLE were used to collect online data. A total of 188 patients participated in the study conducted at a regional teaching hospital in eastern Taiwan, and 51 of them completed the questionnaire twice, with a response rate of 27.1%. Although the second study noted the problem of incomplete data and low response rates, this study shows that online research methodology can still be improved and that using electronic questionnaires for data collection and statistical analysis reduces the risk of errors in online research and saves time in documentation. It is recommended to provide clear and detailed instructions when conducting online surveys and to review them carefully upon completion to ensure the completeness of the data collected.